2012
DOI: 10.1590/s1516-35982012000300003
|View full text |Cite
|
Sign up to set email alerts
|

Digestible lysine requirement of Nile tilapia fingerlings fed arginine-tolysine-balanced diets

Abstract: -This study was conducted to determine the digestible lysine requirements of Nile tilapia fingerlings. Fish (n = 300; average initial weight = 1.44 g) were distributed 15 300-L aquariums, in a completely randomized design with five treatments and three replicates, and fed extruded diets containing 11.3, 13.7, 16.1, 18.4 or 20.8 g/kg of digestible lysine. The arginine:lysine ratio was maintained at 1.3:1. All fish were fed diets containing 281 g/kg of digestible protein and 3,372 kcal digestible energy/kg, hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
3
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 24 publications
3
16
3
2
Order By: Relevance
“…The same observations were made for protein retention, which was highest in fish fed the dietary treatments with a lysine level of 21, 29 and 33 g/kg. This trend of weight gain is consistent with the results reported by earlier workers (Ahmed & Khan, ; Furuya et al., ; Xie et al., ). The reduction in the growth of fish fed higher than the required levels of dietary lysine may be due to the stress caused by excess amount of amino acid in the body of fish leading to extra energy expenditure towards deamination and excretion (Abidi & Khan, ).…”
Section: Discussionsupporting
confidence: 93%
“…The same observations were made for protein retention, which was highest in fish fed the dietary treatments with a lysine level of 21, 29 and 33 g/kg. This trend of weight gain is consistent with the results reported by earlier workers (Ahmed & Khan, ; Furuya et al., ; Xie et al., ). The reduction in the growth of fish fed higher than the required levels of dietary lysine may be due to the stress caused by excess amount of amino acid in the body of fish leading to extra energy expenditure towards deamination and excretion (Abidi & Khan, ).…”
Section: Discussionsupporting
confidence: 93%
“…The literature presents some data related to the essential amino acids requirements for Nile tilapia and according to He et al (2013), lysine and methionine are the most limiting amino acids in diets based on plant origin feed. The lysine requirement for Nile tilapia varies between 1.31 to 2.32% (Furuya et al, 2012Michelato et al, 2016), the values of dietary total lysine that showed the best results in this experiment remained between 1.79 to 1.91%.…”
Section: Resultsmentioning
confidence: 58%
“…As regards Nile tilapia, data on AA requirements were made available long back by Santiago and Lovell (). Some studies have looked specifically into the Lys requirement of Nile tilapia (Liebert & Benkendorff, ) and even on available Lys requirement (Furuya et al, ). However, to our knowledge very few researches have been conducted to estimate dietary lysine requirement of the GIFT strain of Nile tilapia.…”
Section: Introductionmentioning
confidence: 99%